POLA WILLINGNES TO PAY (WTP) KOMODITI TAHU DAN DAGING MASYARAKAT KOTA MALANG - Umi Rofiatin; Taufik Iskandar (Universitas Tribhuwana Tunggadewi, 2017)
Soybeans and meat are the most strategic food commodities and are very risky if it is fully entrusted to the mechanism of the free market. The point is, soy and meat commodities have a very central role in national food policy channels. One of the agricultural ministry targets for 2010 - 2014 is to increase food diversification, especially to reduce rice and wheat consumption. During 2010 - 2014, rice consumption is targeted to fall by 1.5% per year and balanced by increasing in consumption of tubers, animal foods, fruits and vegetables. On the other side, it is also strived to achieve a diverse, nutritious, balanced and safe food consumption pattern as reflected by the increase of Expected Food Pattern (PPH) scores from 86.4 in 2010 to 93.3 in 2014. This study aimed to determine the characteristics of the community in taking decision to buy food products from both tofu and meat sources and to analyze the key factors of consumer’s willingness to buy tofu and meat by using multiple linear regression methods. The results of the study showedthat the characteristics of respondents in the research that affected the gender of respondents were women because married women were the decision makers in terms of household needs. The factors that affected the willingness of consumers to pay tofu were: taste, price and size. Meanwhile, thefactors that affected consumers' willingness to pay for meat were price and shape.